Odpowiedzi

2009-12-20T14:09:42+01:00
1) Oblicz

5(x+3)² - 5(x-4)(x+4)² + (x+1)³=
5(x²+6x+9)-5(x-4)(x²+8x+16)+x³+3x²+3x+1=
5x²+30x+45-5(x³+8x²+16x-4x²-32x-48)+x³+3x²+3x+1=
5x²+30x+45-5x³-20x²+80x+240+x³+3x²+3x+1=-4x³-12x²+113x+276

2) Rzołóż na czynniki

a) a² - 24 =(x-2√6)(x+2√6)
b) 36 + b² = (b+6)²-12b
c) x² - 27= (x-3√3)(x+3√3)
d) x² - 4x+4 =(x-2)²
  • Użytkownik Zadane
2009-12-20T14:44:02+01:00
Zadanie1
5(x+3)² - 5(x-4)(x+4)² + (x+1)³=
5(x²+6x+9)-5(x-4)(x²+8x+16)+x³+3x²+3x+1=
5x²+30x+45-5(x³+8x²+16x-4x²-32x-48)+x³+3x²+3x+1=
5x²+30x+45-5x³-20x²+80x+240+x³+3x²+3x+1=-4x³-12x²+113x+276

Zadanie 2
a) a² - 24 =(x-2√6)(x+2√6)
b) 36 + b² = (b+6)²-12b
c) x² - 27= (x-3√3)(x+3√3)
d) x² - 4x+4 =(x-2)²